Nonlinear relationship between preservation of microstructure and geochemical composition of Pleistocene brachiopod shells from the Ryukyu Islands, southwestern Japan. (16th August 2017) - Yamamoto, Kazuyuki; Takizawa, Mamoru; Takayanagi, Hideko; Asami, Ryuji; Iryu, Yasufumi
Abstract: Stable carbon and oxygen isotope composition of fossilized brachiopod shells serves as an important source to delineate Earth's paleoenvironmental evolution in the Phanerozoic. However, the original isotopic composition is potentially modified by various kinds of diagenesis. To evaluate the extent to which the original isotopic composition of fossilized brachiopod shells is modified by meteoric diagenesis, microstructure, cathodoluminescence (CL) images, and carbon and oxygen isotope composition of fossilized Kikaithyris hanzawai (rhynchonellate brachiopod) shells were examined. The shells were collected from Pleistocene shallow marine carbonates exposed on the Ryukyu Islands, southwestern Japan. The extent of diagenetic alteration is quantitatively evaluated here as both the preservation state of the original shell microstructure and the luminescence/non‐luminescence of shells. Although altered fibers were commonly observed in the brachiopod shells, the original isotopic composition was almost retained. There are no significant differences in the isotopic composition between the luminescent and non‐luminescent shells. There is no direct relationship between the preservation state of the original shell microstructure and the luminescence/non‐luminescence of shells at three of four horizons, indicating that CL images are not necessarily useful for the detection of diagenetic alteration of shells or shell portions. Applying multiple criteria to assessing diagenetic alteration and cross‐checking them are required to distinguish between diagenetically altered and unaltered brachiopod shells. Abstract : To evaluate the extent to which the original isotopic composition of fossilized brachiopod shells is modified by meteoric diagenesis, we examined shell microstructure, cathodoluminescence (CL) images, and carbon and oxygen isotope compositions of fossilized Kikaithyris hanzawai (rhynchonellate brachiopod) shells from Pleistocene shallow marine carbonates exposed on the Ryukyu Islands, southwestern Japan. Although altered fibers were commonly observed in the brachiopod shells, the original isotopic composition was almost retained. There are no significant differences in the isotopic composition between the luminescent and non‐luminescent shells. There is no direct relationship between the preservation state of the original shell microstructure and the luminescence/non‐luminescence of shells at three of four horizons, indicating that CL images are not necessarily useful for the detection of diagenetic alteration of shells or shell portions. Applying multiple criteria to assessing diagenetic alteration and cross‐checking them are required to distinguish between diagenetically altered and unaltered brachiopod shells.